Measurements of confined circular jet - Yeo, Wen Hui (2017)
This report presents findings of the flow characteristics of an air jet issusing from a nozzle of diameter 22mm into a confined space. The jet exit velocity, , was kept at 11±0.2 m/s throughout the experiment. The objectives of this project is to investigate the flow in a confined circular jet and anlayse the velocity profiles of the flow within and after the potential core. Anemometer were used in this project due to its responsiveness and sensitivity, making it suitable for use to measure flow velocity. Measurements were carried out using constant temperature anemometry system with single hot-wire probes. In this study, all probes were fabricated inhouse. Measurements of the mean and root mean square velocities in the streamwise direction were made, from x/D=0.1 to x/D=20. Based on the analysis, it was found that the potential core ended at around x/D=4. It was found that self-preservation for mean velocity profile had been achieved approximately after the potential core. Approximate self-preservation for mean velocity profile is observed at x/D=5 onwards. However, for root mean square velocity profile, self-preservation state was not obtained as no curve plotted show a Gaussian distribution. The centreline velocity decay rate of the confined jet was found to be 0.2597 while the spreading rate of the confined jet was found to be 0.0738. The Reynolds normal stress distribution shows that self-similarity was not reached.